Antibiotic resistance, virulence factors and biofilm formation ability in Escherichia coli strains isolated from chicken meat and wildlife in the Czech Republic - Pavlickova, Silvie; Klancnik, Anja; Dolezalova, Magda; Mozina, Sonja Smole; Holko, Ivan (Journal of environmental science and health. Part. B, Pesticides, food contaminants, and agricultural wastes, 2017)
Attachment of pathogenic bacteria to food contact surfaces and the subsequent biofilm formation represent a serious threat for the food industry, since these bacteria are more resistant to antimicrobials or possess more virulence factors. The main aim of this study was to investigate the correlation between antibiotic resistance against 13 antibiotics, distribution of 10 virulence factors and biofilm formation in 105 Escherichia coli strains according to their origin. The high prevalence of antibiotic resistance that we have found in wildlife isolates could be acquired by horizontal transfer of resistance genes from human or domestic or farm animals. Consequently, these commensal bacteria might serve as indicator of antimicrobial usage for human and veterinary purposes in the Czech Republic. Further, 46 out of 66 resistant isolates (70%) were able to form biofilm and we found out statistically significant correlation between prevalence of antibiotic resistance and biofilm formation ability. The highest prevalence of antibiotic resistance was observed in weak biofilm producers. Biofilm formation was not statistically associated with any virulence determinant. However, we confirmed the correlation between prevalence of virulence factors and host origin. Chicken isolates possessed more virulence factors (66%), than isolates from wildlife (37%). We can conclude that the potential spread of antibiotic resistance pattern via the food chain is of high concern for public health. Even more, alarming is that E. coli isolates remain pathogenic potential with ability to form biofilm and these bacteria may persist during food processing and consequently lead to greater risks of food contamination.
Keywords: kur domácí; Animals; Food Microbiology; Virulence Factors; feces; Feces; Escherichia coli; Chickens; chicken; Food Contamination; lidé; maso; Anti-Bacterial Agents; Meat; virulence factors; bakteriální léková rezistence; biofilm formation; Phylogeny; potravinářská mikrobiologie; kontaminace potravin; Czech Republic; Česká republika; biofilmy; zvířata; antibakteriální látky; fylogeneze; Drug Resistance, Bacterial; Biofilms; faktory virulence; antibiotic resistance; wildlife; Humans